Synthesis of Functionalized δ‐Hydroxy‐β‐keto Esters and Evaluation of Their Anti‐inflammatory Properties. (19th March 2022) - Grosse, Michel; Günther, Kerstin; Jordan, Paul M.; Roman, Dávid; Werz, Oliver; Beemelmanns, Christine
Abstract: δ‐Hydroxy‐β‐keto esters and δ, β‐dihydroxy esters are characteristic structural motifs of statin‐type natural products and drug candidates. Here, we describe the synthesis of functionalized δ‐hydroxy‐β‐keto esters in good yields and excellent enantioselectivities using Chan's diene and modified Mukaiyama‐aldol reaction conditions. Diastereoselective reduction of δ, β‐dihydroxy esters afforded the respective syn ‐ and anti ‐diols, and saponification yielded the corresponding acids. All products were evaluated for their anti‐inflammatory properties, which uncovered a surprising structure‐activity relationship. Abstract : Synthesis of functionalized δ‐hydroxy‐β‐keto esters using Chan's diene and modified Mukaiyama‐aldol reaction conditions. Diastereoselective reduction to syn ‐ and anti ‐diols and saponification yielded the respective acids. All synthesized compounds were evaluated for their 5‐lipoxygenase activity.